Diverticular Abscess Managed With Long-term Definitive Nonoperative Intent Is Safe. Issue 7 (July 2016) - Garfinkle, Richard; Kugler, Aaron; Pelsser, Vincent; Vasilevsky, Carol-Ann; Morin, Nancy; Gordon, Philip; Feldman, Liane; Boutros, Marylise
Abstract : BACKGROUND: Initial nonoperative management of diverticular abscess has become the standard of care; however, the need for elective resection after this index episode is unclear. OBJECTIVE: The purpose of this study was to assess the long-term outcomes of expectant management after initial nonoperative treatment of diverticular abscess. DESIGN: This was a retrospective chart review with prospective telephone follow-up of patients. SETTINGS: The study was conducted at a large tertiary academic colorectal surgery practice in Canada. PATIENTS: Adult patients with CT-documented acute sigmoid diverticulitis complicated by abscess managed nonoperatively from 2000 to 2013 were included. INTERVENTIONS: Long-term definitive nonoperative management of diverticular abscess. MAIN OUTCOME MEASURES: The primary outcome was emergency sigmoidectomy or death from recurrent diverticulitis. Secondary outcomes were recurrent diverticulitis and elective sigmoidectomy for diverticulitis. RESULTS: Of 135 patients with acute diverticulitis complicated by abscess, a total of 73 patients were managed with nonoperative intent and long-term expectant management. The median follow-up was 62 (Q1 to Q3: 28–98) months. After resolution of the index episode, 22 patients [30.1% (95% CI, 19.6%–40.6%)] experienced a recurrent episode of diverticulitis at a median of 23 (range, 9–40) months. Two patients [2.7% (95% CI, –1.0% to 6.4%)] had a recurrent episode with peritonitis that required sigmoidectomy with stoma at 6 and 64 months. Both patients underwent reversal after 4 and 8 months. Seven [9.6% (95% CI, 2.8%–16.4%)] patients experienced a complicated recurrence and underwent an elective sigmoidectomy [median time to colectomy, 33 (range, 16–56) months]. Thirteen patients [17.8% (95% CI, 9.0%–26.6%)] experienced an uncomplicated recurrence, all of whom were managed with continued nonoperative intent [median follow-up, 81 (range, 34–115) months]. No mortality occurred. On multivariate logistic regression, female gender ( p = 0.048) and a previous episode of uncomplicated diverticulitis before the index diverticular abscess ( p = 0.020) were associated with a recurrent episode. LIMITATIONS: This study was limited by its retrospective design and modest sample size. CONCLUSIONS: After initial successful nonoperative management of diverticulitis with abscess, expectant management with nonoperative intent is a safe long-term option with low rates of surgery, especially in the emergency setting. See Video, Supplemental Digital Content 1, on the nonoperative management of diverticular abscess athttp://links.lww.com/DCR/A234 . Abstract : Supplemental Digital Content is available in the text.